Phenotype analysis of CD3+CD16+ lymphocytes in the peripheral blood of pigs - Andrišić, Miroslav (Array, 2020)
The phenotype of porcine peripheral blood T cells and natural killer (NK) cells has been well-studied over the past three decades, though porcine peripheral blood lymphocytes with mixed T/NK-cell phenotype within perforin- and NKp46- positive CD3+ populations have also been identified. Despite the mixed phenotype, both populations showed in vitro NK cell-like major histocompatibility complex-unrestricted cytolysis. In this study, the peripheral blood lymphocytes of 15 crossbreed, 12-week-old pigs of both sexes, were analysed by flow cytometry for the expression of leukocyte surface antigens (cluster of differentiation, CD) that can be found on porcine T cells (CD3, TCR-γδ and CD4), NK cells (CD16) or on both cell populations (CD8α and SLA-DR). We found the presence of a minor population of CD3+CD16+ cells within peripheral blood lymphocytes (2.84%). Peripheral blood CD3+CD16+ lymphocytes consisted of all four subpopulations with respect to the expression of surface antigens CD4 and CD8α; most were CD4-CD8α+ (60.64%) and CD4-CD8α-(36.77%). While the proportion of SLA- DR+ cells within both subpopulations was similar (8.01% of CD3+CD16+CD4-CD8α+ lymphocytes and 7.41% of CD3+CD16+CD4- CD8α- lymphocytes), the proportion of TCR-γδ+ cells was noticeably higher within CD3+CD16+CD4-CD8α+ (43.48%) than CD3+CD16+CD4-CD8α- (16.55%) lymphocytes. When the expression of individual surface antigens was analysed on peripheral blood CD3+CD16+ lymphocytes, most were CD8α+ (62.44%), though some were also TCR- γδ+ (32.56%), SLA-DR+ (7.55%) or CD4+ (2.59%). Expression of CD8α on CD3+CD16+ lymphocytes was not related to co-expression of other surface antigens, though most CD3+CD16+TCR-γδ+ lymphocytes (81.04%) and most CD3+CD16+CD4+ lymphocytes (69.50%) expressed CD8α. Expression of SLA-DR was not related to the co-expression of TCR-γδ or CD8α, or to the co-expression of both antigens (TCR-γδ and CD8α) on CD3+CD16+CD4- lymphocytes.